Evaluación y competencias en diseño arquitectónico (2013)
This paper aims to broaden the outlook of criteria for the evaluation of architectural design or architectural design workshop, since the concept of competence, which is nothing but the manifestation of an autonomous thinking that allows you to solve problems in a specific context. Is specifically designed for teachers who work in this area, essential for the training of architects. It is recognized in academic circles for some decades that the evaluation of projects is being done in an authoritarian manner, unilateral, emotional and arrogant, among other unfavorable features. Complaints are many, but little is said or done to meet the just demands of the students, who are directly affected by the lack of clear rules about it. As teachers design approaches such as the one presented here should encourage the start of a healthy discussion aimed at optimizing the processes and other aspects of the integral formation of future professionals of architecture.